The role of disturbed redox homeostasis in COVID-19 - Marković, Marko (Medicinski podmladak, 2024)
Coronavirus disease (COVID-19) is an acute respiratory disease caused by the SARS-CoV-2 that has spread throughout the world causing millions of deaths. COVID-19 is characterized by the interplay of inflammation and oxidative stress, which may be one of the main mechanisms by which SARS-CoV-2 infection leads to severe acute respiratory failure. Main components of enzymatic antioxidant protection are: superoxide dismutase (SOD), glutathione peroxidase (GPX) and glutathione transferase (GST). Nrf2, a transcription factor that controls the basal activity and coordinated gene expression of specific antioxidant enzymes, is one of the most significant regulatory antioxidant proteins. The activity and antioxidant enzymes and regulatory protein expression is influenced by the polymorphism of the genes that encode them. In this review we tried to acknowledge the role of disturbed redox homeostasis and antioxidant gene profile in COVID-19 susceptibility and disease severity.
Keywords: COVID-19; SARS-CoV-2; redox homeostasis; gene polymorphisms; antioxidant profile